PROGRAM OF ONLINE TRAINING FOR THE DEVELOPMENT OF PSYCHOLOGICAL FEATURES OF WOMEN'S REPRODUCTIVE BEHAVIOR IN MODERN FAMILIES (Psychology Travelogs, 2024)
Article dedicated to the current issue of developing psychological aspects of women's reproductive behavior in modern families and designing an online training program for their psychological growth. Several factors underscore the importance of this research. Contemporary society is undergoing significant changes in gender roles, family structures, and perceptions of motherhood. Simultaneously, the article notes that personal development and psychological well-being of women influence their reproductive behavior. The online training is specifically aimed at increasing positive self-perception, developing personal maturity, and raising awareness of value systems.Taking into account modern technologies and implementing the training in an online format ensures its accessibility to diverse audiences, considering changes in the rhythm of contemporary life. The author emphasizes that the development of positive personality aspects in women will contribute to their active participation in forming healthy and happy families.The article characterizes the main objectives of the training, including forming positive self-perception, developing personal maturity, raising awareness of value systems, and deepening knowledge about the structural components of the maternal image. The application of principles such as systematicity, consideration of age and individual psychological characteristics, alignment of training goals with its content, and the complexity of psychological intervention methods make the program effective and realistic. Recognizing the relevance of the issue in the modern sociocultural context associated with changes in women's roles and family life adds significance and interest to the discussed topic.Introducing the online format allows adapting the training to the demands of contemporary life and ensures accessibility for various user groups. Thus, the article makes a significant contribution to the development of modern psychology, with its results potentially positively impacting the psychological and emotional well-being of women in the face of current challenges.
Keywords: psychological features; women's reproductive behavior; women's health; motherhood; family; family environment; maturity; value orientations; self-perception; interactive training methods